Assessment of fire resistance performance of composite bamboo shear walls - Lily Tambunan; Luis Felipe Lopez; Andry Widyowijatnoko; Yulianto Sulistyo Nugroho (ARTEKS : Jurnal Teknik Arsitektur, 2022)
This study is aimed to examine which configurations of mortar covering give the best fire protection for the bamboo-plaster wall system. The research is done in two stages, first is the non-standardized pre-test stage which results will become the basis for determining the specimen specification. In the second stage, the specimen with the best fire resistance level is tested with a standardized test referred to SNI 1741-2008 and ISO 834-1-1999. Fire resistance performance was measured according to integration and insulation level expressed in minutes. In the pre-testing stage, bamboo-wall configurations with woven bamboo, and mortar plaster on one-sided and two-sided are evaluated according to the burning time and the highest temperature reached on the unexposed side. The pre-testing result shows that the chipped and cracked mortar conditions affect the high temperature of the specimen and the burning of the woven bamboo, and vice versa. In the standardized test in the second stage, it was found that the specimen with one-sided mortar had an insulation and integration level of 30 minutes, while the specimen with two-sided mortar was 120 minutes. These results indicate that the mortar condition and its location affect the fire resistance performance of the bamboo-plaster wall.